The essential oil from Drimys winteri possess activity: Antioxidant, theoretical chemistry reactivity, antimicrobial, antiproliferative and chemical composition - Bruna, Flavia; Fernández, Katia; Urrejola, Felipe; Touma, Jorge; Navarro, Myriam; Sepúlveda, Betsabet; Larrazabal-Fuentes, María; Paredes, Adrián; Neira, Iván; Ferrando, Matías; Osorio, Manuel; Yañez, Osvaldo; et al. (Frontiers in Natural Products, 2022)
The Mapuche and their ancestors have used Drimys winteri in traditional medicine. In the present study, the essential oil extract of Drimys winteri leaves (DW_EO) were characterized chemically and biologically to evaluate its pharmacological activity. In vitro antioxidant activity was assayed, and antitumor activity was evaluated in non-tumor and tumor-cell culture lines. Caenorhabditis elegans was used as a model to evaluate toxicity, and the chemical composition of the essential oil was analyzed by gas chromatography-mass spectrometry. The chemical oil composition was characterized principally of five major terpenes: 4 sesquiterpenes -Eudesmol (39.7%), β-Caryophyllene (33.7%), Elemol (25.9%), α-Eudesmol (0.3%) and 1 diterpene Kaunene (0.4%). By quantum calculations, it was determined that all oils have the ability to capture and yield electrons, which is consistent with the moderate antioxidant activity of DW_EO detected in vitro. Furthermore, by molecular docking is estimated that these oils can bind to proteins involved in the production of oxygen radicals. Of these proteins, CYP2C9 could bind energetically, reaching binding energy between -6.8 and -9.2 kCal/mol for the 5 terpenes studied, highlighting among these β-Caryophyllen and -Eudesmol. DW_EO has effect against H. pylori (MIC 32 μg/mL), S. aureus (MIC 8 μg/mL), E. coli (MIC 32 μg/mL) and C. albicans (MIC 64 μg/mL), β-Caryophyllen and  -Eudesmol (MIC 64 μg/mL) and could selectively inhibit the proliferation of epithelial tumor cell lines but showed low against Caenorhabditis elegans (0.39 to 1.56 μg·mL-1). Therefore, DW_EO may be used as a source of bioactive compounds in novel pharmacological treatments for medical application, agronomics, sanitation, and food.